A cross sectional study to assess the efficacy of glycosylated fibronectin (GlyFn) estimation in prediction of the severity of disease in new onset hypertension in pregnancy from 24 weeks to term - Saswati Sanyal Choudhury; Tina Nath (Barpeta Obstetrics and Gynaecological Society, 2023)
Background: As hypertensive disorders of pregnancy contribute significantly to maternal and neonatal mortality and morbidity, it is very essential to diagnose which cases will eventually have severe disease. Glycosylated fibronectin (GlyFn) is a protein involved in vessel remodelling and inflammation. It is a new biomarker to diagnose severe disease in new onset hypertension. Objectives: The objective is to determine the sensitivity, specificity, positive predictive value and negative predictive value of GlyFn to predict the severity of disease in new onset hypertension in pregnancy from 24 weeks to term. Methodology: The study was carried out in the Department of Obstetrics and Gynaecology, Gauhati Medical College and Hospital from November, 2019 to March, 2020. A total of 50 cases from 24 weeks to term with new onset hypertension were enrolled. The glycosylated fibronectin was estimated in their serum. Final analysis was done on 30 cases, of less than 37 weeks diagnosed as pre-eclampsia. Results: In 30 mothers with PE: 28 true positive, 2 false negative. TPR (true positive rate) or sensitivity = 28/30 = 93.33%; FNR (false negative rate) = 2/30 = 6.67%. Besides, all the high positive cases were associated with adverse maternal and fetal outcomes such as severe hypertension, thrombocytopenia, increased liver enzymes, increased creatinine, neurological complications, pulmonary edema, and low birth weight, prematurity, growth restriction and intrauterine death. Conclusion: All the high positive cases were associated with severe maternal and fetal adverse outcomes and therefore we recommend that cases with GlyFn level more than 600 μg/mL be considered for hospital admission and intensive maternal and fetal monitoring and termination accordingly.